Upcoming SlideShare
×

# Angle between 2 lines

30,449 views

Published on

Describes how to find the angle between 2 lines

1 Comment
2 Likes
Statistics
Notes
• Full Name
Comment goes here.

Are you sure you want to Yes No
• (slide26) -7/4 or -7/3 -_-'

Are you sure you want to  Yes  No
Views
Total views
30,449
On SlideShare
0
From Embeds
0
Number of Embeds
5
Actions
Shares
0
196
1
Likes
2
Embeds 0
No embeds

No notes for slide
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• \n
• ### Angle between 2 lines

1. 1. Angle between 2 LinesPreliminary Extension MathematicsDate: Tuesday 10th May 2011
2. 2. Angle between 2 lines y line l1 has gradient m1 l2 l1 line l2 has gradient m2 ∴ m1 = tan α and m2 = tan β θ α β x 0
3. 3. Angle between 2 lines y line l1 has gradient m1 l2 l1 line l2 has gradient m2 ∴ m1 = tan α and m2 = tan β θ α β x and α +θ =β (Why?) 0
4. 4. Angle between 2 lines y line l1 has gradient m1 l2 l1 line l2 has gradient m2 ∴ m1 = tan α and m2 = tan β θ and α +θ =β α β x (Exterior angle of V) 0
5. 5. Angle between 2 lines y So l2 l1 θ = β −α θ α β x 0
6. 6. Angle between 2 lines y So l2 l1 θ = β −α ∴ tan θ = tan(β − α ) θ α β x 0
7. 7. Angle between 2 lines y So l2 l1 θ = β −α ∴ tan θ = tan(β − α ) θ tan β − tan α = α β 1 + tan β tan α x 0 You will learn this formula later
8. 8. Angle between 2 lines y So l2 l1 θ = β −α ∴ tan θ = tan(β − α ) θ tan β − tan α = α β 1 + tan β tan α x 0 m1 − m2 = 1 + m1m2 Why?
9. 9. Angle between 2 lines y So l2 l1 θ = β −α ∴ tan θ = tan(β − α ) θ tan β − tan α = α β 1 + tan β tan α x 0 m1 − m2 = 1 + m1m2 When tan θ is positive, θ is acute. When tan θ is negative, θ is obtuse.
10. 10. Angle between 2 lines y Thus for two lines of gradient l2 l1 m1 and m2 the acute angle between them is given by θ m1 − m2 tan θ = α β x 1 + m1m2 0 Note that m1m2 ≠ −1 what does this mean?
11. 11. Angle between 2 lines y Thus for two lines of gradient l2 l1 m1 and m2 the acute angle between them is given by θ m1 − m2 tan θ = α β x 1 + m1m2 0 Note that m1m2 ≠ −1 the formula does not work for perpendicular lines
12. 12. Example 1Find the acute angle between y = 2x + 1 and y = −3x − 2(to nearest degree)
13. 13. Example 1Find the acute angle between y = 2x + 1 and y = −3x − 2(to nearest degree) ∴ m1 = 2 and m2 = −3
14. 14. Example 1Find the acute angle between y = 2x + 1 and y = −3x − 2(to nearest degree) ∴ m1 = 2 and m2 = −3 m1 − m2 tan θ = 1 + m1m2
15. 15. Example 1Find the acute angle between y = 2x + 1 and y = −3x − 2(to nearest degree) ∴ m1 = 2 and m2 = −3 m1 − m2 tan θ = 1 + m1m2 2+3 ∴ tan θ = 1− 6
16. 16. Example 1Find the acute angle between y = 2x + 1 and y = −3x − 2(to nearest degree) ∴ m1 = 2 and m2 = −3 m1 − m2 tan θ = 1 + m1m2 2+3 ∴ tan θ = 1− 6 ∴ tan θ = −1
17. 17. Example 1Find the acute angle between y = 2x + 1 and y = −3x − 2(to nearest degree) ∴ m1 = 2 and m2 = −3 m1 − m2 tan θ = 1 + m1m2 2+3 ∴ tan θ = 1− 6 ∴ tan θ = −1 ∴ tan θ = 1
18. 18. Example 1Find the acute angle between y = 2x + 1 and y = −3x − 2(to nearest degree) ∴ m1 = 2 and m2 = −3 m1 − m2 tan θ = 1 + m1m2 2+3 ∴ tan θ = 1− 6 ∴ tan θ = −1 ∴ tan θ = 1 → θ = 45°
19. 19. Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0
20. 20. Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0∴2y = 3x + 7
21. 21. Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0∴2y = 3x + 7 3 7∴y = x + 2 2
22. 22. Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0∴2y = 3x + 7 3 7∴y = x + 2 2 3∴ m1 = 2
23. 23. Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0∴2y = 3x + 7 similarly ∴2y = −4x + 3 3 7∴y = x + 3 2 2 ∴ y = −2x + 2 3∴ m1 = ∴ m2 = −2 2
24. 24. Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0applying the formula m1 − m2 tan θ = 3 1 + m1m2 m1 = m2 = −2 2
25. 25. Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0applying the formula m1 − m2 tan θ = 3 1 + m1m2 m1 = m2 = −2 2 3 +2 ∴ tan θ = 2 1− 3
26. 26. Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0applying the formula m1 − m2 tan θ = 3 1 + m1m2 m1 = m2 = −2 2 3 +2 ∴ tan θ = 2 1− 3 −7 ∴ tan θ = 4
27. 27. Example 2Find the acute angle between 3x − 2y + 7 = 0 and(to nearest degree) 2y + 4x − 3 = 0applying the formula m1 − m2 tan θ = 3 1 + m1m2 m1 = m2 = −2 2 3 +2 ∴ tan θ = 2 1− 3 −7 7 ∴ tan θ = ∴ tan θ = → θ = 60° 4 4
28. 28. Example 3 - by thinking anddrawing....Find the acute angle between y= x+3 and y = −3x + 5(to nearest degree)
29. 29. Example 3 - by thinking anddrawing....Find the acute angle between y= x+3 and y = −3x + 5(to nearest degree) y = −3x + 5 y y= x+3 θ α β x 0
30. 30. Example 3 - by thinking anddrawing....Find the acute angle between y= x+3 and y = −3x + 5(to nearest degree) m1 = 1 → α = 45° y = −3x + 5 y y= x+3 θ α β x 0
31. 31. Example 3 - by thinking anddrawing....Find the acute angle between y= x+3 and y = −3x + 5(to nearest degree) m1 = 1 → α = 45° y = −3x + 5 y y= x+3 m2 = −3 → β = 108° θ α β x 0
32. 32. Example 3 - by thinking anddrawing....Find the acute angle between y= x+3 and y = −3x + 5(to nearest degree) m1 = 1 → α = 45° y = −3x + 5 y y= x+3 m2 = −3 → β = 108° But α +θ =β θ α β x 0
33. 33. Example 3 - by thinking anddrawing....Find the acute angle between y= x+3 and y = −3x + 5(to nearest degree) m1 = 1 → α = 45° y = −3x + 5 y y= x+3 m2 = −3 → β = 108° But α +θ =β θ ∴θ = 63° α β x 0